Chromatic dispersion monitoring of 80 Gbps OTDM data signal via two-photon absorption in a semiconductor microcavity - Donegan, John; Bradley, Louise (My University, 2007)
In this letter, a novel method of chromatic dispersion monitoring via two-photon absorption (TPA) is investigated. A specially designed semiconductor microcavity is employed as a TPA detector for monitoring data signals operating at rates up to80 Gb/s. As the microcavity has a wavelength-dependent response,a single device can be used to monitor multiple channels in a multiwavelength optical telecommunication system.
Keywords: Dispersion monitoring; Microcavity; Wavelength-division multiplexing (WDM); Two-photon absorption (TPA)